2021
DOI: 10.1002/hpm.3371
|View full text |Cite
|
Sign up to set email alerts
|

Perceived self‐efficacy of students and its influence on attitudes and knowledge about HIV/AIDS in Ghana

Abstract: Globally, human immunodeficiency syndrome (HIV) and its accompanying acquired immune deficiency syndrome (AIDS) have long been a public health threat due to the high death toll and the various effects on individuals and societies. Unfortunately, in developing countries such as Ghana, persons living with HIV/AIDS are victims of discrimination and rejection and are often excluded from social activities. Consequently, there is a need for mitigation strategies aimed at reducing the spread of the disease. Indeed, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Specifically, in some populations such as Hispanic women [ 28 ] or young people from Nigeria [ 29 ] levels of condom use self-efficacy would be lower among older people. However, other studies among young people [ 30 , 31 ] have not found statistical differences according to age. Despite these dissimilarities, self-efficacy has demonstrated to be a decisive variable for safe sexual behavior of men and women, in different populations [ 13 14 , 16 , 32 33 ].…”
Section: Introductionmentioning
confidence: 83%
“…Specifically, in some populations such as Hispanic women [ 28 ] or young people from Nigeria [ 29 ] levels of condom use self-efficacy would be lower among older people. However, other studies among young people [ 30 , 31 ] have not found statistical differences according to age. Despite these dissimilarities, self-efficacy has demonstrated to be a decisive variable for safe sexual behavior of men and women, in different populations [ 13 14 , 16 , 32 33 ].…”
Section: Introductionmentioning
confidence: 83%
“…It turns out that perceived self-efficacy plays a key role not only in directly influencing actions and self-regulatory processes, but also (and especially) through its positive impact on cognitive, motivational, decision-making and affective determinants (e.g., Lunenburg, 2011;Opoku et al, 2022). It is therefore conceivable that, just as self-efficacy is known to have a positive impact in domains related to learning, work, well-being, and health (for a review, see Bandura, 1997Bandura, , 2001, then it may also have a positive impact on the attitudes and evaluations people have toward aging.…”
Section: Health-related Self-efficacymentioning
confidence: 99%
“…As such, there is need to raise awareness in communities regarding any new information to make sure that older people living with HIV are constantly supported and cared for effectively. Available literature suggests that there is low knowledge about caring for PLHIV in communities making it difficult to positively improve their health outcomes [ 22 ].This study therefore explored strategies to improve the care of adults 50 years and above living with HIV in Uganda .…”
Section: Introductionmentioning
confidence: 99%